The Role of Personality in Lecturer Engagement and the Effectiveness of Job Satisfaction as an Intervening - Junengsih Junengsih; Nancy Yusnita; Widodo Sunaryo (West Science Business and Management, 2024)
This research to identify methods to enhance lecturer engagement by focusing on job satisfaction and personality factors. The research sample consists of 166 lecturers from private universities in Bekasi. Path analysis and sobel test were employed in the methodology. The finding concludes that: 1) Enhancing personality can boost the engagement of permanent lecturers at private universities. 2) There is an indirect influence of personality on lecturer engagement through job satisfaction, the job satisfaction variable is able to mediate effectively between personality variables and lecturer engagement. It is recommended to strengthen the indicators of these variables to enhance personality through job satisfaction.